2021
DOI: 10.1111/tpj.15221
|View full text |Cite
|
Sign up to set email alerts
|

Expression and processing of polycistronic artificial microRNAs and trans‐acting siRNAs from transiently introduced transgenes in Solanum lycopersicum and Nicotiana benthamiana

Abstract: Targeted gene silencing using small regulatory RNAs is a widely used technique for genetic studies in plants. Artificial microRNAs are one common approach, as they have the advantage of producing just a single functional small RNA, which can be designed for high target specificity and low off-target effects. Simultaneous silencing of multiple targets with artificial microRNAs can be achieved by producing polycistronic microRNA precursors. Alternatively, specialized trans-acting short interfering RNA (tasiRNA) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 80 publications
2
5
0
Order By: Relevance
“…7b ). This is in line with a recent report indicating that polycistronic 5′-hairpins are processed more efficiently than 3′-hairpins 71 . Interestingly, in the case of MIR842/MIR846 duet, the second miRNA but not the first, shows signs of co-transcriptional processing (Extended Data Fig.…”
Section: Resultssupporting
confidence: 93%
“…7b ). This is in line with a recent report indicating that polycistronic 5′-hairpins are processed more efficiently than 3′-hairpins 71 . Interestingly, in the case of MIR842/MIR846 duet, the second miRNA but not the first, shows signs of co-transcriptional processing (Extended Data Fig.…”
Section: Resultssupporting
confidence: 93%
“…Remarkably, when we analyzed polycistronic miRNA duets encoded by a single transcript, we observed that the miRNA hairpin located adjacent to an R-loop was processed co-transcriptionally more efficiently or even the only one showing signs of co-transcriptional processing (Figure 6F). This goes in line with a recent report indicating that polycistronic 5’ hairpins are processed more efficiently than 3’ hairpins (Lunardon et al, 2021). It also reinforces the hypothesis that R-loops between nascent pri-miRNAs and its encoding loci anchor and stabilize the molecule allowing the co-transcriptional processing.…”
Section: Resultssupporting
confidence: 93%
“…The continuous cycle between the host and vector due to their circulative pathway affects prospective agricultural output all over the world. ToLCV particles enter the salivary glands of viruliferous flies while they feed on phloem sap and are then discharged into plants [99].…”
Section: Virus-vector Interactionmentioning
confidence: 99%